Consumidores discriminam trabalhadores por conta própria? Uma análise empírica para o ano de 2014 - Brito, Lorena de Sousa (2018)
This dissertation has the main objective to analyze the possible existence of discrimination of the consumer against self-employed workers in Brazil. Assuming that the individuals most likely to suffer this type of discrimination are those who have more contact with customer in their work process (or who deal with image, success or beauty) a two-level visibility classification has been proposed. In this way, the self-employed were categorized by their skin color and degree of exposition of the occupation (or level of contact with the client), resulting in four comparison groups: high visibility caucasian, high visibility blacks and dark-skinned, low visibility caucasian and low visibility blacks and dark-skinned. The incomes were estimated for each of these groups through quantile regressions applied to the PNAD 2014 microdata. Subsequently, the quantum decomposition method was applied to income differentials to decompose on explained and unexplained components. The main results evidenced the presence of consumer discrimination, which is higher for individuals who have a high degree of contact with the customer. Other results show the predominance of black and dark-skinned individuals in low visibility functions. The distribution of caucasian presentes even greater average and variability than the distribution of non caucasian, a result that meets the theoretical model of consumer discrimination applied here.